New Moon - Meyer, Stephenie, 1973- (New York : Little, Brown and Co., 2006)
When the Cullens, including her beloved Edward, leave Forks rather than risk revealing that they are vampires, it is almost too much for eighteen-year-old Bella to bear, but she finds solace in her friend Jacob until he is drawn into a "cult" and changes in terrible ways.
*Strictly for G7 students and above level use only.
Keywords: Vampires; Werewolves